The Effect Of Liquidity, Profitability, Price To Book Value And Leverage Level On Manufacturing Company Share Prices - Laia, Novia Sri Putri; Bawamenewi, Citra Indah Lestari; Hayati, Keumala (Universitas Gorontalo, 2021)
The main objective of this research is to validate the relationship between the variables of liquidity, profitability, book value (PBV) and the level of leverage and the stock price. This research uses multiple linear analysis methods. There are 165 populations of manufacturing industrial companies listed on the IDX list for the 2016-2019 period. However, the researcher determined several research criteria by applying purposive sampling technique so that this study became 67 samples multiplied by 4 years so that 268 samples were obtained. Analysis of the coefficient of determination shows that the value of 39.5% of the stock price is influenced by the independent variable. Simultaneous test proves that the independent variable can have a positive influence on stock prices. On the other hand, the partial test proves that liquidity and leverage cannot affect stock prices. However, in terms of profitability and PBV are able to influence stock prices positively and significantly.